METODE BERMAIN PERAN UNTUK MENGEMBANGKAN KECERDASAN EMOSIONAL ANAK USIA DINI (Penelitian Single Subject Research Anak Usia 5-6 Tahun di Kabupaten Cirebon) - Susanti, - (2020)
METODE BERMAIN PERAN UNTUK MENGEMBANGKAN KECERDASAN EMOSIONAL ANAK USIA DINI (Penelitian Single Subject Research Anak Usia 5-6 Tahun di Kabupaten Cirebon) This study aims to determine the method of role playing to develop emotional intelligence in early childhood. This research is an experimental study using the Single Subject Research (SSR) approach with the A-B-A design. The research subjects were 4 children aged 5-6 years, namely MRA, FA, AZ and KAZ. Data collection uses the method of performance tests or actions and observations during the implementation of the intervention. The data obtained were analyzed through descriptive statistics and displayed in tables and graphs. The components analyzed are analysis in conditions and analysis between conditions. Based on the results of the research, when the process of role playing during the intervention session showed that the subject experienced an increase in recognizing various kinds of emotions, mimicking the exemplary emotions, namely expressing joy, sadness, anger, fear and empathy, understanding other people's emotions, empathizing with friends and being able to adjust to his friends, so that the value obtained in playing roles in the intervention phase increases. The increase in emotional intelligence experienced by the subject is shown through the increase in the final score at the mean level. Study subjects (MRA) mean level increased from 72.3% at baseline1 (A1) to 77% at the time of intervention (B) and 92% at baseline2 (A2). (FA) the mean level increased from 22.3% at baseline 1 (A1) to 54.25% in intervention (B) and 82% at baseline2 (A2). Subjects (AZ) had their mean level increased from 23.7% at baseline1 (A1) to 50% at the time of intervention (B) and 82% at baseline 2 (A2). And the last research subject (KAZ) also the mean level increased from 19.6% at baseline1 (A1) to 39.5% at the time of intervention (B) and 68.1% at baseline2 (A2). From the results obtained, it can be concluded that the role-playing method can develop early childhood emotional intelligence.